O risco de base, a efetividade do hedging e um modelo para a estimativa da base: uma contribuição ao agronegócio do café em Minas Gerais - Fileni, Dener Hollanda (1999)
The focus ofthis studywas the evaluation of the performance of coffee future contract from the Brazilian Futures Exchange (BM&F) for hedging in Minas Gerais State, Brazil. Tne hedging was measured by its abihty to reduce the price risk ofholding a cash position. Also, the usefulness of future contract to perform coffee inventories, fecilitating the decisions on buying or selling such goods was evaluated. To evaluate the potential of risk reduction it was considered that the hedgers could assume a future position equal to their spot position or, alternatively, thatthe hedgers could use a portfolio model to assume a minimum-risk position. So, the basis risk, the price risk, the hedging effectiveness and the minimum-risk hedge ratio were used to analyze the hedging in coffee market, considering the following factors: the local market, the contract maturity month, the yearandthe hedging duration. To evaluate the utility offuture contract to allocate inventories, the monthly basis was modeled as a function of supply and demand factors, convenience yield, risk premium, üquidity and climate conditions. Altogether, nine variables were used to explain the coffee basis in the following markets: Triângulo Mineiro, Alto Paranaíba, Zona da Mataand Sul de Minas. Tne results pointed out that the basis risk was significatively smaller than the price risk, demonstrating the hedging ability as a risk reducer. Tne hedging bythe portfolio model was also effective at reducing the prices variability, the minimum-variance hedge ratio usually being lower than one. According to the factors in analysis, a higher levei of basis risk was observed for the July and September maturity, indicating larger risks for the anticipatoryhedging. The hedging effectiveness was lower for the Zona da Mata market as wellas for six-month duration. Also, higher leveis ofeffectiveness for the March maturity and an increase of effectiveness in recent years were observed. The results ofthe econometric model ofthe basis showed that a great partofvariability ofthe basis valuewas explained by the independent variables, thus supporting the theory of storage and the usefulness of the coffee future market in Brazil. The model best fitted for the coffee markets of Triângulo Mineiro, Alto Paranaíba and Sul de Minas. For the market ofZona da Mata the model showed an inferior capacity to explain coffee basis. As a final conclusion, the future contract traded by the Brazilian Futures Exchange (BM&F) was considered efficient at reducing the price risk for the coffee agribusiness in Minas Gerais, as well as, the future market provided a real basis for conducting the storage, facihtating the buyingorselling decisions.